Tranexamic acid reduces intraoperative red blood cell transfusion rates in craniosynostosis surgery: a 6-year retrospective analysis - Rositsa Tanova; Petra Vasileva; Dimo Yankov; Dilyan Ferdinandov; Simeon Georgiev; Nikolay Lilyanov (Biotechnology & Biotechnological Equipment)
Surgery for craniosynostosis in children is associated with substantial intraoperative bleeding and the need for blood transfusions. Recent studies have supported the efficacy of tranexamic acid (TXA) in reducing blood loss and transfusion requirements. The records of 72 patients under 18 months of age who had undergone 113 surgeries for non-syndromic craniosynostosis in a single institution for 6 years were retrospectively analyzed. The transfusion requirements in infants with and without TXA administration were compared. The concept of patient blood management before and after TXA implementation in practice was also examined. The rate of intraoperative packed red blood cells (PRBC) transfusion was significantly lower in the TXA than in the non-TXA group (26.7% vs. 83%, p < 0.001). The volume of intraoperatively transfused PRBC was also lower in the TXA group compared to the non-TXA group (mean 68.25 mL vs. 101.91 mL, p < 0.001), as was the weight-adjusted volume (mean 11.2 mL/kg vs. 15 mL/kg, p = 0.002). There were no significant differences in the rate and volumes of postoperative PRBC transfusion between groups. The volume of intraoperatively transfused PRBC was dependent on TXA administration, but not on the affected suture and type of intervention. We found that while in the pre-TXA period all patients were transfused intraoperatively, the frequency of intraoperative transfusions in the post-TXA period was reduced by 40.9% even in the patients who had not received TXA. TXA seems to effectively reduce the intraoperative transfusion requirements in children undergoing craniosynostosis surgery. The optimal blood management in this patient population remains to be further evaluated.